2020
DOI: 10.1038/s41598-020-71610-w
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost green recyclable biomaterial for energy-dependent electrical switching and intact biofilm with antibacterial properties

Abstract: A highly cost-effective recycled biomaterial extracted from lime peel has been made biocompatible and has been coated on a commercial fluorine-doped tin oxide (FTO) substrate of glass using the spin coating method. Structural, morphologic, electronic, and antibacterial measurements were thoroughly characterized as a green biomaterial thin film using X-rays (XRD), PL, FTIR, Raman, SEM, HRTEM, AFM, I–V, and antibacterial diffusion techniques. The comprehensive analysis of structures of recyclable waste in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The incorporation of semiconductor nanomaterials in polymeric networks of hydrogels enhanced the photothermal behavior via nonradiative relaxation phenomena or lattice vibration . The defect chemistry describes the electronic structure of the host material where electron-trapped states capture electrons in shallow bulk states below the conduction band, and captured electrons lose energy in the form of lattice vibrations or phonons (heat). , Irshad et al also extensively investigated the role of electron-captured states below conduction bands toward hopping charge carrier concentration. Nevertheless, lower mechanical strength, fragile natures, and viability of hydrogels toward real-world applications are still limited. Therefore, the fabrication of noble hydrogels possessing a mechanically strong and robust nature is still entailed and a major area for research direction. …”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of semiconductor nanomaterials in polymeric networks of hydrogels enhanced the photothermal behavior via nonradiative relaxation phenomena or lattice vibration . The defect chemistry describes the electronic structure of the host material where electron-trapped states capture electrons in shallow bulk states below the conduction band, and captured electrons lose energy in the form of lattice vibrations or phonons (heat). , Irshad et al also extensively investigated the role of electron-captured states below conduction bands toward hopping charge carrier concentration. Nevertheless, lower mechanical strength, fragile natures, and viability of hydrogels toward real-world applications are still limited. Therefore, the fabrication of noble hydrogels possessing a mechanically strong and robust nature is still entailed and a major area for research direction. …”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 b represents the vapor condensation process from muddy wastewater and condensed water collection. According to WHO, statistics shows that 80% diseases spread by unsafe drinking water such as organic and inorganic toxins [ 4 , 35 , 36 , 37 ]. Mostly these toxins impurities are found in trace levels and many are responsible for the toxicity factors of the complex mixture, particularly wastewater, and are the principal cause of some of the world’s most dangerous bacterial infections.…”
Section: Resultsmentioning
confidence: 99%
“…To date to produce nanomaterials, several attempts have been made by a variety of biological waste resources to generate different types of nanomaterials that could be of low cost, eco-friendly, and extremely active for usage in the manufacture of pharmaceuticals and biomedicines. 8 Previously, various studies have also reported vegetable waste peel aqueous extract mediated silver nanoparticles including our previous findings like Pisum sativum, 8 and others like Momordica charantia, 9 and Raphanus sativus 10 lime, 11 etc. The eco-friendly and economical vegetable and fruit peels are generally considered waste products.…”
Section: Introductionmentioning
confidence: 62%